Tradisi Ruwatan: Sejarah, Prosesi, dan Makna Filosofis (Sebuah Kajian Foklor) - Suprapto Suprapto; Dhani Irfanda Bayu Saputra; M Imam Dairobi (Ruang Kata, 2026)
The ruwatan tradition in Javanese culture is a profound spiritual ceremony, intended to balance an individual's life through purification and liberation from negative influences. The purpose of this research is to explore and understand the ruwatan tradition in a deeper context, both in terms of its history, practices, and philosophical meaning. This research is ethnographic, aiming to describe the circumstances of a community group closely related to culture. Data collection in this study used interviews and relevant literature review. The data obtained were analyzed through verification and interpretation stages to describe the history, practices, and philosophical meaning of ruwatan in the village of Kambeng Slahung, Ponorogo. Research shows the origins of this tradition are linked to the mythology of Batara Kala, who is believed to influence bad luck. Ruwatan is primarily aimed at the Sukerta group, who are considered born with bad luck and need to be physically and spiritually cleansed. The ceremony involves various stages, from tirakatan (templation), obligatory bathing, hair and nail cutting, to slametan (prayer offerings) and a murwakala (wayang) performance, all of which are imbued with symbolic and philosophical meaning. The philosophical meaning of ruwatan encompasses self-purification and the relationship between humans and nature and supernatural powers, with the hope that the individual undergoing the ritual will be protected from suffering and misfortune. Besides serving as a form of religious belief, this tradition also strengthens social bonds and preserves Javanese cultural values rich in local wisdom